The Relationship between Students’ Learning Interest and Students’ Problem-Solving Skill of Eighth-Grade Students in Learning Mathematics - Anggun Siska Hamidah; Desyarti Safarini TLS (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2020)
This study aims to determine the relationship between students’ learning interests and students’ problem-solving skill of eighth-grade students in learning mathematics. Correlational research design is applied in this study whether to determine the relationship between the two variables. The sample consists of 43 eighth-grade students at one of Junior High School in Jakarta academic year 2019/2020. In general, the eighth-grade students dominate at an average level of students’ learning interest and students’ problem-solving skill with a percentage of 79.07% and 72.09%, respectively. Based on the SPSS analysis, it is obtained that was 0.405, which describe a relationship between students’ learning interest and students’ problem-solving skill of eighth-grade students in learning mathematics. The students’ learning interest and students’ problem-solving skill have a moderate positive correlation. Since the data are collected online, there will be factors that can be considered as factors that influence students’ mathematical problem-solving skill. Thus, the students’ learning interest can explain about 16.4% of the total variation in the students’ mathematical problem-solving skill.